Oxygen Isotopes in Authigenic Clay Minerals: Toward Building a Reliable Salinity Proxy. Issue 3 (11th February 2020) - Gebregiorgis, D.; Deocampo, D. M.; Longstaffe, F. J.; Simpson, A.; Ashley, G. M.; Beverly, E. J.; Delaney, J. S.; Cuadros, J.
Abstract: Most clay minerals in sedimentary environments have traditionally been considered to be of detrital origin, but under certain conditions, authigenic clay minerals can form at low temperature through the transformation of precursor clays or as direct precipitates from lake water. Such clay minerals can hold important information about the prevailing climatic conditions during the time of deposition. We present the first quantitative reconstruction of salinity in paleolake Olduvai based on the oxygen‐isotope composition of authigenic clay minerals. We provide a framework illustrating that the isotopic signature of authigenic lacustrine clay minerals is related to the isotopic composition of paleo‐waters, and hence to paleosalinity. This new paleosalinity proxy shows that the early Pleistocene East African monsoon was driven by combinations of precession and obliquity forcing and subsequent changes in tropical sea surface temperatures. Such quantitative lacustrine paleosalinity estimates provide a new direction of research for modeling ecosystem change based on an ecologically relevant parameter. Plain Language Summary: Lake sediments contain a rich archive of information about past climate change. Clay minerals in such sediments, in particular, can potentially provide important insight into changes in humidity and aridity in the terrestrial environment by recording changes in precipitation as reflected in lake salinity. Until now, the climate records possibly provided by such clays have not been studied in detail. Here, we have used the oxygen‐isotope compositions of clay minerals formed in lake water to investigate past salinity changes in paleolake Olduvai during the early Pleistocene Epoch (~1800–1920 kyr). Isotopes are varieties of an element that have different masses. The two isotopes of oxygen in clay minerals that we measured reflect the lake water composition from which they formed. The isotopic ratios of the lake water, in turn, reflect in predictable ways the extent of lake water evaporation and associated changes in salinity. We interpret the lake salinity changes to reflect changes in intensity of the East African monsoon. We show that the weakening or strengthening of the early Pleistocene East African monsoon was related to changes in the Earth's orbit. This relationship involves complex pathways related to changes in sea surface temperature in the ancient tropical oceans. Key Points: First quantitative reconstruction of salinity in paleolake Olduvai based on oxygen‐isotope measurements of authigenic clay minerals Combined precession and obliquity forcing of the early Pleistocene East African monsoon Early Pleistocene East African monsoon likely controlled by SST changes in the tropical oceans